Pembelajaran Nilai Budi Pekerti Pada Siswa Sekolah Dasar Melalui Upacara Tradisi di Tawangmangu - Lestari, Winda (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2022)
Moral values can be obtained anywhere. Included in the traditional ceremonies that exist in the community by interpreting it as a noble ancestral teaching. Learning moral values based on regional content or local wisdom will develop an attitude of loving local culture that is currently starting to be left behind by the wave of digital technology. This study aims to describe the moral values contained in the Dhukutan traditional ceremony in Tawangmangu District, Central Java. The data of this research is in the form of a transcription of direct observation and in-depth analysis which is then analyzed using content analysis techniques so that the results of the research on the values of mutual respect, self-control, democratization and problem solving are appropriate to be taught as early as possible to elementary school students.